Extracellular matrix and egg coats - Litscher, Eveline; Wassarman, Paul M. (Current topics in developmental biology, 2018)
Extracellular Matrix and Egg Coats, Volume 130, the latest release in the Current Topics in Developmental Biology series, highlights new advances in the field, with this new volume presenting interesting chapters on The Human Egg's Zona Pellucida, the Structure of Zona Pellucida Module Proteins, The Fish Egg's Zona Pellucidam The Chicken Egg's Zona Pellucidam The Marsupial Egg's Zona Pellucida, the Evolution of Zona Pellucida Proteins, The Mouse Egg's Zona Pellucida, Aspects of ECM, ECM and Morphogenesis, Collagen fibril assembly and function, The Ear's Tectorial Membrane, ECM and Cell Fate, and the Aspects of ECM.